How "influence" do media, facilities, and learning interests influence students' economic learning outcomes? - Nursaid, Nursaid; Nuraini, Sri; Novitasari, Dwi Rizki (Assyfa Journal of Multidisciplinary Education, 2023)
Providing ample facilities encourages active student participation and enhances learning outcomes. Evaluating the adequacy of educational resources is crucial for maximizing student achievement. Student performance is influenced by available resources and other factors, including family economics, peer influence, and societal factors. Adequate facilities are linked to higher academic achievement, while their lack can impede learning and reduce student performance. This research employs a quantitative methodology to analyze the impact of media usage, facilities, and student learning interests on their motivation and outcomes in economics. Data was collected from primary and secondary sources, involving a sample of 124 participants, including 31 class XI students from a private high school in East Java. Results indicate a positive relationship between media usage and learning facilities with learning motivation. However, there is no significant relationship between Learning Interest and Learning Motivation nor a direct relationship between media, facilities, and learning outcomes. A unidirectional relationship exists between learning interest, motivation, and outcomes. Additionally, a significant correlation is found between students' learning preferences and exposure to learning media, whereas facilities do not show a positive correlation with academic interests.